A radiological study on the relationship between the novel acromial angle and rotator cuff tears - Zhipeng Hou; Jiabao Dong; Wenzhao Shang; Quqiao Wan; Haoxin Huang (Scientific Reports)
Abstract To investigate the relationship between the novel acromial angle and rotator cuff tears through imaging studies. We retrospectively selected 148 patients who underwent complete imaging examinations including scapular outlet X-rays and shoulder MRIs from January 2023 to September 2024 at our hospital. Based on whether the subjects had rotator cuff tears, they were divided into an injury group and a normal group, and the differences in the novel acromial angle between the two groups were compared. The novel acromial angle in the normal group was (149.1 ± 5.957)°, while in the injury group, it was (142.3 ± 6.558)°, showing a statistically significant difference between the two groups (P < 0.001). The probability of rotator cuff injury was 79.07% for individuals with a novel acromial angle smaller than the average in the injury group. The novel acromial angle in the injury group was generally smaller than that in the normal group. A novel acromial angle smaller than the average was associated with a higher probability of rotator cuff injury, and smaller angles were more likely to lead to more severe rotator cuff tears. Therefore, the novel acromial angle may serve as a simple and objective method to predict the probability of rotator cuff tears.